Manufaktur Heater Menggunakan Bahan Pipa Steam untuk Mesin Stirling Tipe Gamma Skala Kecil - Kurniawan, Eprian; Jufrizal, Jufrizal; Nurdiana, Nurdiana (CV. IRA PUBLISHING, 2024)
The design and manufacturing of a heater for a Gamma-type Stirling engine on a small scale require careful consideration of key factors to ensure thermal efficiency and optimal performance. This study utilized AutoCAD software to design the heater precisely according to operational requirements. The heater functions as a critical component that transfers heat from the source to the working fluid positioned at the front of the Stirling engine. The manufacturing process employed carbon steel, chosen for its ability to withstand high temperatures and ensure even heat distribution. Test results demonstrated that the manufactured heater could achieve an average temperature of 484.50 °C, reflecting its stability and optimal heat distribution during operation. This stability is a crucial indicator of the heater's thermal efficiency and reliability in supporting the Stirling engine's performance. The study confirms that the applied design process, material selection, and manufacturing techniques successfully produced a heater that meets the design specifications. Thus, this research significantly contributes to developing heater technology for small-scale Stirling engine applications.